Developing early literacy 0-8 from theory to practice - Bower, Virginia (SAGE Publications, 2014)
'Developing Early Literacy presents an interesting range of literacy-related topics which address issues of current importance to early years practice and, in places, question current thinking. There is an excellent balance of theoretical background and case study examples which would make this a relevant and practical text for both students and early years professionals.'